Theoretical insights into the protonation states of active site cysteine and citrullination mechanism of Porphyromonas gingivalis peptidylarginine deiminase. Issue 8 (25th May 2017) - Zhao, Chenxiao; Ling, Baoping; Dong, Lihua; Liu, Yongjun
ABSTRACT: Porphyromonas gingivalis peptidylarginine deiminase (PPAD) catalyzes the citrullination of peptidylarginine, which plays a critical role in the rheumatoid arthritis (RA) and gene regulation. For a better understanding of citrullination mechanism of PPAD, it is required to establish the protonation states of active site cysteine, which is still a controversial issue for the members of guanidino‐group‐modifying enzyme superfamily. In this work, we first explored the transformation between the two states: State N (both C351 and H236 are neutral) and State I (both residues exist as a thiolate–imidazolium ion pair), and then investigated the citrullination reaction of peptidylarginine, using a combined QM/MM approach. State N is calculated to be more stable than State I by 8.46 kcal/mol, and State N can transform to State I via two steps of substrate‐assisted proton transfer. Citrullination of the peptidylarginine contains deamination and hydrolysis. Starting from State N, the deamination reaction corresponds to an energy barrier of 18.82 kcal/mol. The deprotonated C351 initiates the nucleophilic attack to the substrate, which is the key step for deamination reaction. The hydrolysis reaction contains two chemical steps. Both the deprotonated D238 and H236 can act as the bases to activate the hydrolytic water, which correspond to similar energy barriers (∼17 kcal/mol). On the basis of our calculations, C351, D238, and H236 constitute a catalytic triad, and their protonation states are critical for both the deamination and hydrolysis processes. In view of the sequence similarity, these findings may be shared with human PAD1–PAD4 and other guanidino‐group‐modifying enzymes. Proteins 2017; 85:1518–1528. © 2017 Wiley Periodicals, Inc.